Pulmonary functions and life quality assessment results two years after COVID-19 comparison with the sixth month results - Mustafa İlteriş Bardakci; Esin Nagihan Ozturk; Müfide Arzu Ozkarafakili; Hüseyin Ozkurt; Uğur Yanc; Dilek Sevgi Yıldız (Journal of Infection in Developing Countries)
Introduction: We aimed to investigate the effects of COVID-19 on patients 24 months after severe COVID-19 pneumonia.